THE ADVANTAGES OF USING FAIRY TALES IN THE LESSONS - Normurodov, Kamol (Журнал иностранных языков и лингвистики, 2023)
The article considers the material of fairy tale texts as a valuable resource in the study of foreign languages, in particular English. Fairy tales are a fertile source of early foreign language education. They clearly express the identity of the people, their culture, customs, moral principles, features of national life and way of life. At the same time, the fairy tales of the English-speaking countries, along with their cultural diversity, reflect universal human values ​​that are instilled in children from an early age. Examples of possible methods of using fairy tales in the article are given to increase the motivation of students in teaching communicative skills.